Association between unilateral functional ankle instability, limited ankle dorsiflexion range of motion and low back pain - Abdelhaleem, Mahmoud Diab; Grase , Mariam Omran; Aly, Sobhy Mahmoud; Abdallah, Ehab Ali (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
There is growing evidence that supports the correlation between incidence of ankle dysfunction and low back pain (LPB). Although the spine and ankle seem like distant regions of the body, they are functionally connected by the lower extremity kinematic chain. The aim of the current study was to investigate the association between functional ankle instability (FAI), limited ankle dorsiflexion (DF) range of motion (ROM) and (LPB). One hundred two subjects with chronic ankle sprain pain participated in this study. The mean ± SD age, weight, height, and BMI of the study group were 43.5 ± 12.96 years, 85.27 ± 14.22 kg, 172.9 ± 8.45 cm, and 28.59 ± 4.72 kg/m². LPB was measured by Visual Analogue Scale (VAS), FAI was measured by the anterior drawer test and DF ROM was measured by the lunge test. All statistical analyses were performed using the Statistical Package for Social Studies (SPSS) version 25 for Windows. There was no statistically significant association between pain and age, pain and BMI, pain, and sex (p > 0.05). There was a statistically significant association between pain and drawer test (odd ratio 5.68, p = 0.02) and a statistically significant association between pain and DF ROM (odd ratio 1.16, p = 0.01). The current study supported previous studies recommending FAI and limited ankle DF ROM as a factor in LPB. The authors suggest conducting similar studies with a larger number of participants and include functional measures scales or questionnaires to increase the validity and generalizability of the results.